2021
DOI: 10.3389/fevo.2021.774744
|View full text |Cite
|
Sign up to set email alerts
|

Winners and Losers: How Woody Encroachment Is Changing the Small Mammal Community Structure in a Neotropical Savanna

Abstract: Years of fire suppression, decreases in herbivores, and global climate change have led to shifts in savannas worldwide. Natural open vegetation such as grasslands and shrublands is increasing in wood density, but the effects for small mammals are not well understood. While most of the mammal studies from the Brazilian Cerrado are concentrated in the core area of this large Neotropical savanna, its southern portions are suffering from biome shifting through woody encroachment. Herein, we surveyed a small mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
(153 reference statements)
1
8
0
Order By: Relevance
“…Although less studied, fine-scale habitat variables (e.g., grass cover, canopy cover, number of termite mounds, and soil type) might also be related with Cerrado small mammal richness and abundance patterns at local scale Furtado et al, 2021). Vegetation structure was shown to influence savanna vertebrate diversity, especially by altering the availability of food resources, refuge sites, presence of competitors, and/or predators, as well as their dispersal capacity (Kutt and Woinarski, 2007;Price et al, 2010;Sirami and Monadjem, 2012;Ribeiro et al, 2019).…”
Section: Discussion Species Richness and Diversity Across Scalesmentioning
confidence: 99%
“…Although less studied, fine-scale habitat variables (e.g., grass cover, canopy cover, number of termite mounds, and soil type) might also be related with Cerrado small mammal richness and abundance patterns at local scale Furtado et al, 2021). Vegetation structure was shown to influence savanna vertebrate diversity, especially by altering the availability of food resources, refuge sites, presence of competitors, and/or predators, as well as their dispersal capacity (Kutt and Woinarski, 2007;Price et al, 2010;Sirami and Monadjem, 2012;Ribeiro et al, 2019).…”
Section: Discussion Species Richness and Diversity Across Scalesmentioning
confidence: 99%
“…Similarly, 118 species of small mammals occur across the Cerrado savanna region of Brazil, with local richness as high as 26, yet N. lasiurus represented >20% of individuals captured in the aggregate of 96 field studies (Mendonça et al, 2018); this, and only a handful of other small-mammal species are the focus of habitat-related studies we found for the current review, meaning that responses to habitat perturbations by most native Cerrado small-mammal species are unknown. Importantly, Furtado et al (2021) fills some of this knowledge gap for seven species of small mammals of the Cerrado. Finally, as we mentioned earlier, we found no studies of habitat effects on small mammals from South Asian TSE at all.…”
Section: Conservation Implications and Future Research Needsmentioning
confidence: 98%
“…While not directly examining fire, Furtado et al (2021) found that shrub encroachment resulting from years of fire suppression in the southeastern Cerrado is changing the small-mammal community composition from open-country or grassland specialists (e.g., Necromys lasiurus and Cryptonanus spp.) to closed-canopy forest specialists (e.g., Didelphis albiventris and Oligoryzomys nigripes).…”
Section: Neotropicsmentioning
confidence: 99%
“…In the absence of controlled fires and herbivory, many open savannas are becoming dominated by trees (transitioning into cerradão), a phenomenon known as the "wood encroachment" (Stevens et al 2017). Specialists in open savannas such as the Pampas Deer, Marsh Deer, and the rodents Clyomys laticeps, Cerradomys scotti, and marsupials such as Cryptonanus chacoensis are negatively affected by increasing wood encroachment (Furtado et al 2021).…”
Section: What Is the Future Of Mammal Diversity In São Paulo State?mentioning
confidence: 99%